The role of education in enhancing collaboration between state and non-state actors in combating human trafficking - I Made Anom Wiranata; Putu Ratih Kumala Dewi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study explores the role of education in enhancing collaboration between state and non-state actors in combating human trafficking in Indonesia. Using a qualitative approach and literature review, the research examines scholarly articles, policy documents, and reports published between 2010 and 2024, systematically selected from Scopus, Google Scholar, and JSTOR, based on their relevance to education, collaboration, and human trafficking. The analysis focuses on educational programs aimed at raising public awareness, strengthening law enforcement capacities, and fostering cooperation among stakeholders such as government agencies, NGOs, and civil society organizations. The findings reveal that education plays a crucial role in improving public understanding of human trafficking, enhancing law enforcement responses, and promoting collaboration. However, the review identifies contradictions regarding the sustainability and effectiveness of educational initiatives, particularly in marginalized communities, and the gap between awareness-raising and long-term institutional collaboration. These inconsistencies suggest that educational interventions are often fragmented and poorly integrated into broader anti-trafficking frameworks. The study concludes that while education is essential for prevention and intervention, it must be part of a coordinated anti-trafficking strategy, including stronger legal frameworks, victim protection, and policy reforms. Future research should focus on longitudinal evaluations and comparative analyses of law enforcement training models.